A ZnCl2 water-in-salt electrolyte for a reversible Zn metal anode. Issue 100 (29th November 2018) - Zhang, Chong; Holoubek, John; Wu, Xianyong; Daniyar, Aigerim; Zhu, Liangdong; Chen, Cheng; Leonard, Daniel P.; Rodríguez-Pérez, Ismael A.; Jiang, Jia-Xing; Fang, Chong; Ji, Xiulei
Abstract : We report a low-cost water-in-salt electrolyte (WiSE), of 30 m ZnCl2, which enables a dendrite-free Zn metal anode to possess a high coulombic efficiency. Abstract : We report a low-cost water-in-salt electrolyte, of 30 m ZnCl2, which enables a dendrite-free Zn metal anode to possess a high coulombic efficiency (CE). In asymmetric Zn‖Zn cells with a limited mass of plated Zn as the working electrode, the ZnCl2 WiSE improves the average CE of the Zn anode to 95.4% from 73.2% in 5 m ZnCl2 .